2004
DOI: 10.2174/1381612043384754
|View full text |Cite
|
Sign up to set email alerts
|

PET Imaging of Beta-Adrenoceptors in Human Brain: A Realistic Goal or a Mirage?

Abstract: Beta-adrenoceptors are predominantly located in the cerebral cortex, nucleus accumbens and striatum. At lower densities, they are also present in amygdala, hippocampus and cerebellum. Beta-2 sites regulate glial proliferation during ontogenic development, after trauma and in neurodegenerative diseases. The densities of beta-1 adrenoceptors are changed by stress, in several mood disorders (depression, excessive hostility, schizophrenia) and during treatment of patients with antidepressants. A technique for beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 222 publications
(163 reference statements)
1
37
0
Order By: Relevance
“…In order to study an association that includes a reduction of the depression score, the reduction may be minor or absent if the depression score is within normal range at baseline. This has already been discussed in a comprehensive manner [26]. In the present study, the effects of beta-blockers that are observed in the group as a whole are more pronounced when analysed in the subgroup of patients with an elevated depression score at baseline.…”
Section: Strengths and Weaknessessupporting
confidence: 61%
See 1 more Smart Citation
“…In order to study an association that includes a reduction of the depression score, the reduction may be minor or absent if the depression score is within normal range at baseline. This has already been discussed in a comprehensive manner [26]. In the present study, the effects of beta-blockers that are observed in the group as a whole are more pronounced when analysed in the subgroup of patients with an elevated depression score at baseline.…”
Section: Strengths and Weaknessessupporting
confidence: 61%
“…This may be compared to the minimum clinical relevant antidepressant effect for pharmacological treatment of patients with overt depression (e.g. MDI score ≥ 20 at baseline) which was 0.3 according to the US Federal Drug Administration [26]. As such, it may be concluded that the achieved clinical effect size by this non-pharmacological intervention was clinically relevant for IHD patients in general, and even more so for the patients with an elevated depression score.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…The antidepressant effect exerted by the drug desipramine determined in an unpredictable chronic mild stress model in mice was reversed by propranolol [25]. Furthermore, according to several studies, β-adrenoceptors may be involved in the action of antidepressants [26][27][28][29].…”
Section: Discussionmentioning
confidence: 97%
“…in the brain, myocardium, tumor and other regions or organs . Some reviews concerning promising PET probes including the [ 18 F]fluoroalkyl ligands for molecular imaging have been published [79][80][81]. [13,26,[92][93][94][95][96][97][98][99].…”
Section: Application Of [ 18 F]fluoroalkylation For Positron Emissionmentioning
confidence: 99%